Test de Autoevaluación de Meditación Transcendental: a psychometric study of Peruvian school children and adolescents (Revista Innova Educación, 2024)
The specific, as well as holistic, effects of practicing the Transcendental Meditation technique have been thoroughly documented. Findings associated with the practice have included a range of physiological, psychological and sociological benefits, but have also encompassed measures of general health, well-being and human development. However, few if any indigenous test instruments have been used to gather these data. In Perú, a test instrument called Test de Autoevaluación de Meditación Transcendental (i.e., Self-Assessment Test of Transcendental Meditation) designed to measure benefits of Transcendental Meditation in school children and adolescents has been deployed with some degree of success. The test was designed about 25 years ago to measure physical health, cognitive health, emotional health, and school performance, and has been completed by about 50,000 primary and secondary school students since its introduction. Recently published studies have documented the results.  But the test has never been psychometrically evaluated. The purpose of the present study therefore was to rigorously assess the reliability and construct validity of the instrument using exploratory factor analysis and confirmatory factor analysis. Results of these analyses revealed a five latent factors—more alertness and energy, improved physical and mental health, enhanced cognitive performance, enhanced emotional and behavioural self-regulation, and more fulfilling interpersonal relationships—which reliably predicted an overall scale of health in students. Application of a revised Test de Autoevaluación de Meditación Transcendental is now ready for further use in Perú and, with translation, other school settings.
Keywords: Transcendental Meditation; psychometric testing; exploratory factor analysis; school; Peru